Determinants of Taxpayer Compliance: The Role of Coretax, Socialization, Sanctions, and Risk Preference Moderation - Nadya Nurkhasanah; Agung Yulianto; Nelia Fariani Siregar (Indonesian Journal of Islamic Economics and Finance, 2026)
This study investigates how Coretax, tax socialization, and tax sanctions influence individual taxpayer compliance, while also assessing the potential moderating role of risk preference in these relationships. Employing a quantitative approach, data were obtained from questionnaires completed by 379 individual taxpayers registered at KPP Pratama Indramayu, and the resulting data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4. The results indicate that Coretax utilization and tax socialization have positive and significant effects on taxpayer compliance, whereas tax sanctions do not significantly influence compliance. Furthermore, risk preference is also found to significantly weaken the positive relationships between Coretax utilization and compliance, as well as between tax socialization and compliance, although it does not moderate the link between tax sanctions and compliance. This research adds to the taxation literature by extending the Theory of Planned Behavior through the incorporation of risk preference as a behavioral factor influencing the effectiveness of digital taxation systems and tax education initiatives. The findings also provide practical insights for tax authorities in designing more targeted compliance strategies.